The Effect of Nutrition Counseling and RESTTM Diet also Occupational Factors on Weight Loss among Hospitals Nurses with Excessive Weight Nutritional Status (Study in The Occupational Health Hospital of West Java Province) - Novi Oktaviani; Astrid Sulistomo; Agus Sugiharto,; Dian Novita Chandra; Amilya Agustina (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: Nurse has a risk to get an excessive weight nutritional status that can increase the risk of serious health problems, such as heart disease, hypertension and diabetes mellitus. The intervention of nutrition counseling and diet are expected to lose weight in people with excessive weight nutritional status. This study aimed to determine the effectiveness of nutrition counseling and the implementation of Rendah Energi, Seimbang dan Teratur (REST) diet on weight loss among hospital nurses with excessive weight nutritional status in the hospital.Methods: The study was conducted at Occupational Health Hospital of West Java with 22 nurses as study subjects with excessive weight nutritional status, implemented nutrition counseling intervention, a RESTTM Diet and also used the Bouchard questionnaire, OSI-RTM questionnaire and food record sheets.Results: The greatest average weight loss after receiving nutrition counseling and implementing a RESTTM Diet occurred in the 12th week of the last observation. It was 2.6 kg with 95% CI=1.3-3.9 kg. Based on the bivariate test showed gender had a significant effect on the average weight loss. The male nurses had greater average weight loss than female nurses (p=0.038). The average weight loss of male nurses was 3.1 ± 1.7kg and female nurses 1.6 ± 1.3kg. Meanwhile, the effect of occupational factors on weight loss after receiving nutrition counseling and implementing the RESTTM Diet did not show a significant effect, such as job position (p=0.948), the number of working hours (p=0.220), work shift schedule (p=0.692) and work stress (p=0.813).Conclusions: There was an effect of nutrition counseling and RESTTM Diet during 12 weeks on weight loss among the hospital nurses with excessive weight nutritional status in the hospital.